Reconnecting Youth: Promoting emotional competence and social support to improve academic achievement. (March 2017) - Dougherty, Danielle; Sharkey, Jill
Abstract: Previous research indicates that students who drop out of high school are at risk for a number of negative outcomes. Both ecological and individual risk factors contribute to students' propensity for dropout. This study examined the effectiveness of a targeted dropout prevention program at improving academic achievement and investigated whether improved social support and emotional competencies partially mediated the association between intervention participation and student outcomes. A sample of 110 middle and high school students (55 intervention participants and 55 students in a matched control group) completed surveys investigating their social-emotional assets and schools provided academic data for participants. Structural equation modeling revealed that students who participated in the program had higher academic achievement compared to the control group. Prior levels of academic achievement moderated the effectiveness of the program with students with low initial levels of academic achievement benefiting more. Emotional competencies and social support did not mediate the relation between participation and achievement. The intervention was related to improved academic achievement among participants; however, the means by which it was effective was unclear. Given the evidence that the program was more effective for some students than others, targeting interventions to meet specific needs of students may be advantageous. Highlights: Reconnecting Youth (RY), a dropout prevention program, was used to improve academic achievement among at-risk youth. RY was most effective for youths with the lowest levels of prior achievement. Emotional competencies and social support did not explain relation between participation in RY and achievement.